Too big to cheat? An empirical study of the impact of firm size on earnings management in Vietnam - Trang, Dr. Do Thi Van; Mai, Dr Tran Ngoc (The journal of contemporary issues in business and government, 2021)
Earning management has been an ongoing problem throughout the world nowadays. Determinants of earning management and their impacts are still a controversial topic. This study therefore aims to measure the impact of firm size and sale growth volatility on the manipulation among corporations in Vietnam. Firm size is evidenced positively related to the misstatements, the larger the size is, the greater motivation they have with the earnings. Sale growth volatility, which has not been widely used before, is significantly associated with the earning management. Firms with unstable sales appear to engage in earning manipulation.